MicroRNA Profiling during Craniofacial Development: Potential Roles for Mir23b and Mir133b - Ding, Hai-Lei; Hooper, Joan E.; Batzel, Peter; Eames, B. Frank; Postlethwait, John H.; Artinger, Kristin B.; Clouthier, David E. (Frontiers in Physiology, 2016)
Defects in mid-facial development, including cleft lip/palate, account for a large number of human birth defects annually. In many cases, aberrant gene expression results in either a reduction in the number of neural crest cells (NCCs) that reach the frontonasal region and form much of the facial skeleton or subsequent failure of NCC patterning and differentiation into bone and cartilage. While loss of gene expression is often associated with developmental defects, aberrant upregulation of expression can also be detrimental. microRNAs (miRNAs) are a class of non-coding RNAs that normally repress gene expression by binding to recognition sequences located in the 3’ UTR of target mRNAs. miRNAs play important roles in many developmental systems, including midfacial development. Here, we take advantage of high throughput RNA sequencing (RNA-seq) from different tissues of the developing mouse midface to interrogate the miRs that are expressed in the midface and select a subset for further expression analysis. Among those examined, we focused on four that showed the highest expression level in situ hybridization analysis. Mir23b and Mir24.1 are specifically expressed in the developing mouse frontonasal region, in addition to areas in the perichondrium, tongue musculature and cranial ganglia. Mir23b is also expressed in the palatal shelves and in anterior epithelium of the palate. In contrast, Mir133b and Mir128.2 are mainly expressed in head and trunk musculature. Expression analysis of mir23b and mir133b in zebrafish suggests that mir23b is expressed in the pharyngeal arch, otic vesicle and trunk muscle while mir133b is similarly expressed in head and trunk muscle. Functional analysis by overexpression of mir23b in zebrafish leads to broadening of the ethmoid plate and aberrant cartilage structures in the viscerocranium, while overexpression of mir133b causes a reduction in ethmoid plate size and a significant cleft. These data illustrate that miRs are expressed in the developing midface and that Mir23b and Mir133b may have roles in this developmental process.